Dental Consultation Communication Checklist: Translation and Validation of the Persian Version - Afsaneh Pakdaman; Razagh Ahmadpour; Maryam Serajzadeh (Islamic Dental Association of Iran, 2015)
Background and Aim: Attention to proper communication with patients in dental setting is important in the quality of care. The purpose of the present study was to translate the Dental Consultation Communication Checklist (DCCC) to Persian and validate the Persian version. Materials and Methods: In this descriptive analytical study, the standard 'forward-backward' method was used to translate the English version of the checklist to Persian. Face and content validity were assessed and the reliability was scored by calculating the intra-class correlation coefficient (ICC) and Cronbach's alpha. A number of 4th, 5th and 6th year dental students completed the checklist. The mean score in each domain was calculated and compared using one way ANOVA test. Results: Of 245 dental students, 83% responded (n=204). The content validity index (CVI) was 0.83 and 0.93 for the appropriateness and clarity, respectively. Reliability analysis showed satisfactory result (ICC=0.86, Cronbach's alpha=0.89). The self-reported positive response to question "I introduced myself and explained my role" was weak compared to all other questions. There was no statistically significant difference in the scores obtained by the three groups of dental students. Conclusion: The Persian version of DCCC is a valid and reliable instrument for use in the clinical setting.